2017
DOI: 10.2116/analsci.33.35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Casting Solvent on Interfacial Molecular Structure and Proton Transport Characteristics of Sulfonated Polyimide Thin Films

Abstract: Two sulfonated polyimide (SPI) thin films were prepared with water and THF/water mixed solvents, respectively. The SPI thin film prepared with THF/water showed more than 5 times higher proton conductivity than that prepared with water mixed solvent at low relative humidity (RH) and 298 K. In this study, polarized optical microscopy (POM), grazing incidence small angle X-ray scattering (GISAXS), and p-polarized multiple angle incidence resolution spectrometry (pMAIRS) were carried out to investigate liquid crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials. In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials. In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…16−37 Structure and transport properties in confined polymer thin films differ drastically from those of the bulk materials because of interactions between the polymer and substrate surface. 38,39 For example, a study of Nafion thin films demonstrated that the degree of the phase segregation, water uptake, and proton conductivity decreased concomitantly with decreasing film thickness. 26,34,35 Recent investigations have assessed structural controls of the proton conductive channels undertaken for the enhancement of proton conductive properties.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high proton conductivity of polymer electrolytes, various polymer electrolyte membranes such as perfluorosulfonated polymers, sulfonated block copolymers, and graft copolymers have been examined based on a concept of the well phase-separated hydrophilic channels composed of hydrophobic backbones and hydrophilic parts. The proton conductivity of polymer electrolyte membranes is closely related to several parameters such as acidity, number of sulfonic acid groups, main chain and side chain structures, and membrane morphology. From a different perspective, structural confinement effects of polymer electrolyte thin films have been reported. Structure and transport properties in confined polymer thin films differ drastically from those of the bulk materials because of interactions between the polymer and substrate surface. , For example, a study of Nafion thin films demonstrated that the degree of the phase segregation, water uptake, and proton conductivity decreased concomitantly with decreasing film thickness. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In recent polymer research fields, taking advantage of the interface extends the molecular design such as the oriented structure and organized structure for the highly proton conductive materials. In this Feature Article, I proposed the concept of molecular orientation to improve proton conductivity for various proton conductive polymers using the interface of substrate surfaces. The interface can modify the degrees of freedom for polymer structures through interaction with functional groups, wettability, and the surface charge between the substrate surface and polymers. Some proton conductive polymers exhibit an oriented structure by the fabrication of thin films.…”
Section: Introductionmentioning
confidence: 99%